TINJAUAN YURIDIS AUTOPSI ULANG KORBAN TINDAK PIDANA DAN KEKUATAN HUKUM PEMBUKTIANNYA - Riandra, Daffa Azta; Erdiansyah, Erdiansyah; Hidayat, Tengku Arif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
In criminal cases, evidence is always a principal and crucial matter,because sometimes in processing a case. Witnesses, victims and perpetrators aresilent, meaning they do not want to provide information. Because it makes proofsomething important. In practice, autopsies are performed more than once. Thefunction of the autopsy is as a criterion in determining the criminal liability of theperpetrator. If there is a re-autopsy whether the judge ignores one of them, and ifthere are two autopsy results how the judge assesses each autopsy because notnecessarily the results of the re-autopsy are correct. This raises the uncertainty ofthe position of the re-autopsy results for the purposes of trial evidence. Then inthe forensic regulation in Indonesia, it does not clearly regulate re-autopsy,including the conditions that must be met if you want to do a re-autopsy, the timelimit for re-autopsy and how many times a re-autopsy is carried out. Theregulation of re-autopsy in Indonesia is not regulated in legislation and has notclearly regulated the position of re-autopsy evidence and its legal certainty.This research is classified into normative juridical research. The data usedare primary data and secondary data consisting of primary legal materials,secondary legal materials, and tertiary legal materials. The data collectiontechnique uses the literature review method, namely describing and analyzingdata from several sources such as laws, books and opinions of criminal lawexperts. This research was then analyzed descriptively qualitatively. The inferencetechnique used is by doing a deductive mindset.The results of this study are that re-autopsy is valid because it strengthensthe search for material truth of a criminal act and re-autopsy re-autopsy forevidentiary purposes depends on the judge's consideration in assessing the resultsof the re-autopsy. Because the value of the evidentiary power is free, it is hopedthat the judge will consider justice, expediency and legal certainty in decidingcriminal cases so that there will be no misguided decisions.Keywords : Autopsy,Victim,Criminal Act,Evidence